Pengaruh waktu inokulasi virus kerdil kedelai terhadap tingkat keterbawaannya pada biji yang dihasilkan = Effect of Soybean Stunt Virus Inoculation Time to - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
The objectives of the research was to determine the effect of SSV(Soybean Stunt Virus) inoculation in varies plant age of soybean to infected seed yield. The reasearch was conducted : 1) the field reasearch is the treatment of soybean in 3 different time of inoculation ie., 10, 28 , and 45 days after planting respectively, and without inoculation of soybean plant by Randomized Complete Design method, 2) the laboratory reasearch is to detection of SSV on seed by I-ELISA method. The result of the research showed that the stage of plant growth had different sensitivity of SSV infection. On soybean plant that infected with SSV earlier would be caused: 1) increased the number of diseased plant and more severe the symptom, 2) decreased of the plant height, the number of internode, the number and the weight of pods, the number of seeds in its pods, the weight and the size of seed (weight on 100 seeds), 3) increase the number of mottled seed, 4) higher virus concentration that seed borne.